2012
DOI: 10.4103/0973-6131.98223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of holistic yoga program on anxiety symptoms in adolescent girls with polycystic ovarian syndrome: A randomized control trial

Abstract: Context:Yoga techniques practiced for varying durations have been shown to reduce state anxiety. This was never assessed in adolescents with polycystic ovarian syndrome (PCOS).Aims:To compare the effect of a holistic yoga program with the conventional exercise program on anxiety level in adolescents with PCOS.Settings and Design:Ninety adolescent (15-18 years) girls from a residential college in Andhra Pradesh, who satisfied the Rotterdam criteria, were randomized into two groups.Materials and Methods:Anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The self-rated safety of TRM hinges on the widespread belief that the herbal preparations are natural and consequently safe for human use. Studies report that users of TRM actually perceive it to be safer alternatives than the scientific medicine,33, 34 and therefore highly acknowledged among students and the general population. This finding provides evidence to suggest that students have positive attitudes towards TRM.…”
Section: Discussionmentioning
confidence: 99%
“…The self-rated safety of TRM hinges on the widespread belief that the herbal preparations are natural and consequently safe for human use. Studies report that users of TRM actually perceive it to be safer alternatives than the scientific medicine,33, 34 and therefore highly acknowledged among students and the general population. This finding provides evidence to suggest that students have positive attitudes towards TRM.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically significant improvements in emotion, body weight and menstrual problems ( d > 0.5) Exercise and medicine Harris-Glocker et al [ 43 ] RCT 36 Obese, adolescent females with PCOS Age range: 12–18 years BMI 34.8 kg/m 2 PCOSQ 6 months MET group: Oral contraceptive with metformin + motivation + diet + exercise (weekly, 60-min group exercise) PBO group: Placebo + motivation + diet + exercise (weekly, 60-min group exercise) PCOSQ total scores significantly improved in both groups, across all domains, between baseline and conclusion. No significant difference between the groups Ladson et al [ 41 ] RCT 22 Obese, adolescent females with PCOS MET group: age 16.1 ± 1.5 years BMI 37.1 ± 5.8 kg/m 2 PBO group: age 15.4 ± 1.2 years BMI 35.9 ± 6.6 kg/m 2 PCOSQ 6 months MET group ( n = 11, DO: 1): metformin + 150 min/week of exercise + low-calorie diet PBO group ( n = 11, DO: 3): placebo + 150 min/week of exercise + low-calorie diet Improvements in overall quality of life in both groups (data not reported) Ladson et al [ 42 ] RCT 114 Obese females with PCOS MET group: age 29.0 ± 4.5 years BMI 38.0 ± 7.8 kg/m 2 PBO group: age 28.8 ± 4.6 years BMI 38.3 ± 8.0 kg/m 2 PCOSQ 6 months MET group ( n = 55, DO: 33): metformin + low-calorie diet + 150 min/week of exercise PBO group ( n = 59 , DO: 43): placebo + low-calorie diet + 150 min/week of exercise Non-significant improvements in domains of quality of life (weight and emotion only) for both groups Other interventions Nidhi et al [ 39 ] RCT 90 Healthy adolescent females with PCOS Exercise: age 16.2 ± 0.9 years BMI 21.2 ± 3.0 kg/m 2 Yoga: age ...…”
Section: Resultsmentioning
confidence: 99%
“…However, there was a modest improvement in depression and anxiety score in women treated with acupuncture, compared with typical exercise and with the control group. In another study comparing a traditional exercise program with yoga among a group of adolescents [ 39 ], state and trait anxiety decreased following both interventions. The remaining research included intervention studies with exercise included as a part of a multi-factor lifestyle modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yogahelps to open up the pelvis and promotesrelaxation while Pranayam is a powerful technique that calms the mind.Studies conducted haverevealed that a holistic yoga program showed significant results as compared to the conventional physical exercises followed by two random, controlled groups for a duration of one hour per day for 12 weeks in the following parameters. a) Improvement in glucose, lipid and insulin and insulin resistance values [59] b) Reduction in symptoms of anxiety [60] c)Reduction of Anti-Müllerianhormone(AMH), Luteinizing hormone(LH), Testosterone, modified Ferriman and Gallwey score(mFG) for hirsutism and an improvement in menstrual frequency. [61] Weight loss is the most essential part of treatment as it rectifies hormonal imbalance, elevates the insulin and sex hormone binding globulin levels and reduces the testosterone levels.…”
Section: 2yogaandpranayam Therapymentioning
confidence: 99%